Participation in the under-18 Euroleague Next Generation Tournament does not predict attaining NBA, Euroleague, or Eurocup - Carvalho, Humberto M. (2022)
We examined whether participation and individual performance in the under-18 Euroleague Next Generation Tournament (NGT) predicted a future contract with an NBA, Euroleague, or Eurocup squad. Data from 1446 players between 2002–2003 and 2011–2012 seasons were considered. We considered information about each player, including country, the number of games played, and performance index rating (PIR). We tracked the players’ highest club level attained in their adult careers. We used a multilevel ordinal regression with a cumulative model in a fully Bayesian framework to examine the probability of the players playing in the NGT attaining the NBA, Euroleague, or Eurocup. Furthermore, we explored in the model if PIR in the NGTwas a relevant predictor of achieving the highest club level in adult careers. From the total sample, only a very small percentage attain the NBA (20 in 1446, 1.4%), Euroleague (103 in 1446, 7.2%), and Eurocup (60 in 1446, 4.2%). The results highlight that a very small number of players with a very high PIR per game in the NGT had a higher chance to play in the NBA, Euroleague, or Eurocup. The probability of attainment of NBA and Euroleague for the population of highly selected basketball players playing the under-18 NGTin the first 10 years of the NGTwas small. Hence, caution is warranted when assuming the effectiveness of current talent development models, even at the late stages of young players’ development, often labelled as young elite players.